Peningkatan Pemahaman Mahasiswa dalam Penulisan Karya Ilmiah Melalui Kegiatan Menulis Skripsi Itu Mudah - Resista Vikaliana; Irwansyah (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
Writing scientific papers for undergraduate students in the form of a thesis, it is often difficult to understand the rules of writing.  This was confirmed by the survey at the beginning of the activity. The purpose of this activity is that there is an increase in the student participating in the writing of thesis scientific papers. The method used in this activity is a series of workshops during August-October 2020. The workshops are conducted interactively online through a zoom meeting. After providing materials and simulations through workshops, the activity was continued with individual consultation and mentoring through the WhatsApp group. The training participants consisted of 99 students in the First Series, then 70 students in the Second Series. Workshop participants come from various campuses. To find out the impact of the activity, at the end of the activity an online survey was conducted. In general, the participants felt helped by the activity of this workshop. However, because the speakers has a social and humanities background, participants from the technology science family are not specifically served